Prediksi potensi deviasi pola ruang kawasan permukiman berbasis cellular automata di Kecamatan Mapanget, Kota Manado - Sela, Rieneke Lusia Evani; Malik, Andy Anton Mangopa; Tilaar, Sonny; Lestari, Nadira Astuti (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
Mapanget District is one of the administrative parts of Manado City which has service functions, namely housing and new settlements, tourism, and trade and services. The Mapanget District is part of the new city planning in the 2015–2019 RPJMN to account for unequal development in the city core. Predicting the development of residential land use is crucial to avoid uncontrollably detrimental effects on suburban communities. To forecast land development over 20 years, from 2022 to 2042, this study will employ spatial analysis based on the Geography Information System-Cellular Automata and weighting analysis using the Analytic Hierarchy Process (AHP) technique to analyze potential deviations in the spatial pattern development of Manado City settlements, particularly Mapanget District. The software used for this research's simulation procedure is LanduseSim 2.3.1, QGIS, and Archmap 10.8. According to the projection results, residential land use will vary during the following 20 years, starting in 1956.75 Ha, or a 201% increase, resulting from the most important driving factor, which is closeness to existing towns. 1106.79 Ha is the possible deviation depending on the direction of the spatial pattern plan for residential structures. It is advised to plan tall buildings, particularly for settlements, as the current residential land in Mapanget District exceeds both the carrying capacity and the land capacity as of 2042, according to the prediction results.